Evaluation of chitosan crystallinity: A high-resolution solid-state NMR spectroscopy approach. (15th December 2020) - Facchinatto, William Marcondes; Santos, Danilo Martins dos; Fiamingo, Anderson; Bernardes-Filho, Rubens; Campana-Filho, Sérgio Paulo; Azevedo, Eduardo Ribeiro de; Colnago, Luiz Alberto
Highlights: 13 C CPMAS method was successfully used to quantify the crystallinity of chitosans; The accuracy of 13 C SSNMR is higher than conventional X-ray diffraction method; 13 C SSNMR did not require amorphous standards to quantify the crystallinity of chitosans. Abstract: We propose a novel approach relied on high-resolution solid-state 13 C NMR spectroscopy to quantify the crystallinity index of chitosans (Ch) prepared with variable average degrees of acetylation ( D A ¯ ) from 5% to 60 % and average weight molecular weight ( M ¯ w ) ranged in 0.15 × 10 6 g mol −1 –1.2 × 10 6 g mol −1 . The Dipolar Chemical Shift Correlation (DIPSHIFT) curve of the C(6)OH segment revealed increased mobility dynamic, which induced different distribution from trans- to -gauche conformations in relation to C(4). Indeed, 1 H- 13 C Heteronuclear Correlation (2D HETCOR) showed that distinguished C4 chemical shifts correlates with the same aliphatic protons. The short-range ordering can be assigned to C4/C6 signals on 13 C CPMAS and, for our case, the deconvolution procedure between disordered and ordered phases revealed increasing crystallinity with D A ¯, as confirmed by SVD multivariate analysis. This work extended the knowledge regarding the use of 13 C CPMAS technique to predict the crystallinity of chitosans without the use of amorphous standards.